Young Adult Medical Cannabis Patients in Florida: Gender Differences in Characteristics of use, Experiences at Dispensaries, and Association With Health-Related Problems - Lorenzo, Elise (Journal of drug issues, 2025)
In recent years there has been an increase in cannabis use among adults in the U.S., which corresponds with changes in state-level laws making cannabis available for medical/recreational use. While cannabis became available for medical use in Florida in 2014, it was not until a ban on smoking cannabis was lifted in 2019 that the number of patients began to increase. The data for the current study are the Florida Young Adult Cannabis Study and focus on 415 medical cannabis patients (MCP). We identified several significant differences between male and female MCP. Female MCP initiated regular cannabis use at a younger age and reported more frequent cannabis use. Female MCP were more likely to endorse self-treatment motives while male MCP were more likely to endorse recreational motives. As Florida is one of the largest and most diverse states in the U.S., research on MCP is needed to inform policy.